Islamic Education, SDGs, and Javanese Syncretism in Kidung Rumekso by Sunan Kalijaga - Mukhlis Fathurrohman; Ngatmin Abbas (Universitas Muhammadiyah Surakarta, 2026)
Objective: This study explores the intersection of Islamic education, the Sustainable Development Goals (SDGs), and Javanese cultural syncretism through Kidung Rumekso by Sunan Kalijaga. It aims to examine syncretism as a cultural–pedagogical strategy in the Islamization of Java, focusing on how Islamic teachings are integrated with Javanese traditions and their implications for culture-based Islamic education aligned with SDGs, particularly inclusive and quality education. Theoretical framework: The study employs the concept of syncretism supported by hermeneutic and phenomenological approaches to analyze the integration of Javanese cosmology and Islamic monotheism within the text. Literature review: Existing scholarship indicates that Islamization in Java occurred adaptively through cultural accommodation; however, specific studies positioning Kidung Rumekso as an epistemological reconstruction remain limited. Methods: This research uses a qualitative philosophical method with a hermeneutical-phenomenological approach, examining textual content, relevant literature, and historical-cultural contexts. Results: The findings reveal that Kidung Rumekso represents a profound model of Javanese-Islamic syncretism operating across three dimensions: (1) theological, reflected in the alignment of Manunggaling Kawula Gusti with the principle of tawhid; (2) ritual, seen in the transformation of traditional chants or mantras into Islamic prayers; and (3) symbolic, demonstrated through the use of Javanese cultural symbols to communicate Islamic teachings contextually. These dimensions illustrate how religious values are transmitted in culturally resonant forms, supporting socially sustainable education. Implications: This model contributes to the development of contextual Islamic education that is adaptive, inclusive, and rooted in local wisdom, aligning with SDGs’ emphasis on cultural sustainability and equitable learning. Novelty: The study offers a new perspective by interpreting Kidung Rumekso as an epistemological reconstruction bridging Javanese mysticism and Islamic orthodoxy, rather than merely a form of cultural accommodation.